Cyber Warfare and Global Power Politics - Ms. Afeera Firdous (CISS Insight Journal, 2020)
Every technological advancement brings more power to the countries acquiring these capabilities and a new set of threats as well. Along with that, the struggle for power among states also begins. The development of computer and information technology is not an exception to this phenomenon. New threats to personal and national interests emerge as states acquire and develop this new technology. This paper analyzes power asymmetry in major states developing non-contact and stand-off capabilities in warfare such as in the cyber domain. It also examines the international discussion on cyber governance and cyber arms control, cyber-related policy documents and military units, and state-sponsored cyber-attacks. In the end, the paper describes the regional context of cyber geopolitics i.e. how both, India and Pakistan, are evolving their respective capabilities in the cyber domain.